Solo leveling. 2 - Chugong; Torres, J., 1969- (Yen Press, 2021)
"Ever since he woke up in the hospital, Jinwoo's been thrown into a world of cryptic messages, daily quests, and strange dungeons overflowing with creatures he's never even heard of. As he tests out his new abilities, it starts to sink in that he is no longer the Weakest Hunter of All Mankind. Maybe he can finally attain what he's always wanted- enough power to protect himself- but a run-in with an unexpected foe forces Jinwoo to consider just how far he's willing to go to obtain it!"--Amazon.